Match running performance in Brazilian professional soccer players: comparisons between successful and unsuccessful teams - Aquino, R.; Gonçalves, L. G.; Galgaro, M.; Santi Maria, T.; Rostaiser, E.; Pastor, A.; Nobari, H.; Rodrigues Garcia, G.; Moraes-Neto, M. V.; Nakamura, F. Y. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background This study aimed to compare the match running performance between bottom- and top-ranked teams in professional soccer players over the 2020 season of the Brazilian National 2nd Division League. In addition, this study verified the independent and interactive effects of playing position and contextual factors on running outputs between these teams.